Stewards of memory : the past, present, and future of historic preservation at George Washington's Mount Vernon - Cadou, Carol Borchert; Pecoraro, Luke J.; Reinhart, Thomas A. (University of Virginia Press, 2018)
"This book focuses on historic preservation issues at George Washington's Mount Vernon"--